Characteristics of Breast Cancer Patients at RSUP Dr. M. Djamil Padang - Ahmad Aqeed Izreen; Darwin, Eryati; Khambri , Daan (Fakultas Kedokteran, Universitas Andalas, 2025)
Background: Breast cancer is the most common cancer in women in Indonesia and worldwide. Among the proven risk factors are age, age of menarche, age of menopause, history of hormonal birth control use, number of parities, breastfeeding history, family history of breast cancer and smoking history. Objective: This study was conducted to determine the risk factors and distribution of breast cancer patients based on risk factors at Dr. M. Djamil Padang Hospital in 2022-2023. Methods: This study is a retrospective descriptive study. The study sample was breast cancer patients at RSUP Dr. M. Djamil Padang and was selected using consecutive sampling technique. Data was taken from the patient's medical record and processed using the SPSS application to obtain a distribution of patients based on risk factors. Results: The results of the study obtained a sample according to the inclusion and exclusion criteria were 52 people. The majority of patients were aged 40–49 (40.4%), menarche at the age of 13 and 14(50%), not yet menopause (26.9%), using hormonal birth control for 5 years and more (42.3%), having 2 children (34.6%), breastfeeding for 24 to 35 months (50%), not having a family with breast cancer (88.5%) and never smoked but was a passive smoker (92.3%). Conclusions: Exposure to risk factors increase the incidence rate of breast cancer. Keyword: reproductive period, family history, smoking